2020
DOI: 10.4317/jced.57463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebral cortex activation induced by tactile stimulation between natural teeth and implants

Abstract: Background The purpose of this study was to assess the cortical-level sensory differences between natural teeth with a periodontal membrane and dental implants. Material and Methods We used functional near-infrared spectroscopy (fNIRS) to measure brain activity in the cerebral cortex of 12 patients who had both natural teeth and dental implants in the lower molar region. Painless vibratory tactile stimulation was performed on both the natural teeth and the dental implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Separate from masticatory performance and cognitive performance, generalized gray matter volume reduction was found among people with narcolepsy, a sleeping disorder resulting from an orexin deficiency [ 11 ], which is a hormone that also enhances appetite [ 12 ]. However, it was reported that there was no significant difference in the brain responses to vibrotactile stimuli applied to a natural tooth or a dental implant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Separate from masticatory performance and cognitive performance, generalized gray matter volume reduction was found among people with narcolepsy, a sleeping disorder resulting from an orexin deficiency [ 11 ], which is a hormone that also enhances appetite [ 12 ]. However, it was reported that there was no significant difference in the brain responses to vibrotactile stimuli applied to a natural tooth or a dental implant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%